Discrepancy Principle and Convergence Rates in Regularization of Monotone Ill-Posed Problems - Nguen, Byong (Ukrains’kyi Matematychnyi Zhurnal, 2003)
The convergence rates of the regularized solution as well as its Galerkin approximations for nonlinear monotone ill-posed problems in a Banach space are established on the basis of the choice of a regularization parameter by the Morozov discrepancy principle.